Implementation of The Reciprocal Teaching Model in Elementary School’s Islamic Education Subjects - Dalimunthe, Ardiana; Amini; Nurzannah (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
The purpose of this study was to analyze the application of the Reciprocal Teaching model in improving student learning outcomes in Islamic Religious Education (PAI) subjects in class VI of SDN 102062 Bangun Bandar. This Reciprocal Teaching Model, which involves interactive dialogue-based teaching strategies between teachers and students, is applied to build students' understanding skills, problem solving, and reflective abilities regarding teaching materials. This study uses a qualitative research type using a case study approach, which focuses on the application of the Reciprocal Teaching method in class VI SDN 102062 Bangun Bandar. Data collection in this study was obtained through interviews, observations, documentation, or focus group discussions (FGD). Data analysis techniques obtained following interactive miles-huberman include: data reduction, data presentation, and drawing conclusions. Data analysis techniques with triangulation and member crosscheck. The results of this study indicate that the application of the reciprocal teaching model is effective in increasing learning activities for elementary school students in grade VI, totaling 14 males and 21 females. The form of implementation is reviewed from, first, students are grouped to discuss and teach the material to their classmates. Second, training students' critical thinking skills. Third, training students' communication skills. Fourth, teachers can evaluate students' mastery of the material. Fifth, achieving students' learning completion targets. The obstacles in implementing the reciprocal teaching model are the lack of seriousness of some students in preparing themselves to become teachers for their classmates and some students often laugh at friends who act as teachers, thus ruining the learning atmosphere. The solutions implemented include providing students with an understanding of the importance of their role as teachers, establishing a supportive classroom culture with clear rules, and active supervision by teachers to maintain a conducive classroom atmosphere.